Atmospheric-temperature-based cooling system control for electronic devices using internet of things. Issue 1 (2nd January 2020) - Mahesh, C.; Arumugam, Arthi; Kannan, E.; Logesh, K.
ABSTRACT: The operating temperature of electronic devices plays a vital role in its durability of operation. When the electronic chip surface temperature increases beyond threshold limit, it undergoes breakdown and starts to malfunction; upon continuous operation, it gets melt down. Generally, cooling arrangements such as fan or A/C are provided to maintain the temperature. The low operating temperature also leads to problems such as excessive energy consumption and noisy operation. The surface temperature must be maintained in accordance with the surrounding temperature and the control should be independent of the operator, such an intelligent system can be developed by internet of things (IOT). IOT with smart gateways can provide the possible solution; this paper deals with one such intelligent system implementation and its performance. The proposed system considers the atmospheric temperature to control the cooling system. The smart system is estimated to save 6% of power consumption and also simultaneously reduces the noisy operation.